2010
DOI: 10.1161/hypertensionaha.110.152892
|View full text |Cite
|
Sign up to set email alerts
|

Management of High Blood Pressure in Blacks

Abstract: Abstract-Since the first International Society on Hypertension in Blacks consensus statement on the "Management of HighBlood Pressure in African American" in 2003, data from additional clinical trials have become available. We reviewed hypertension and cardiovascular disease prevention and treatment guidelines, pharmacological hypertension clinical end point trials, and blood pressure-lowering trials in blacks. Selected trials without significant black representation were considered. In this update, blacks wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
236
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(250 citation statements)
references
References 169 publications
(166 reference statements)
11
236
0
3
Order By: Relevance
“…Also, these patients were followed for only 2 years and the main treatment drug was a long‐acting calcium channel blocker (CCB). Diuretics, widely considered first line along with CCBs in most professional society guidelines, were used in only 12% of the patients 7, 11, 12, 13. While not reaching statistical significance, subgroup analysis suggested that intensive treatment goals may be beneficial in patients <75 years old while adopting a more liberal strategy may be safer in those ≥75 years old 10…”
Section: Jnc 8 Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, these patients were followed for only 2 years and the main treatment drug was a long‐acting calcium channel blocker (CCB). Diuretics, widely considered first line along with CCBs in most professional society guidelines, were used in only 12% of the patients 7, 11, 12, 13. While not reaching statistical significance, subgroup analysis suggested that intensive treatment goals may be beneficial in patients <75 years old while adopting a more liberal strategy may be safer in those ≥75 years old 10…”
Section: Jnc 8 Recommendationmentioning
confidence: 99%
“…In the black population with hypertension, CCBs and thiazide diuretics generally tend to be favored as initial therapy over renin‐angiotensin system blockers 13, 14, 45. The evidence for this recommendation comes from ALLHAT, which showed in prespecified subgroup analysis that black patients treated with lisinopril had higher rates of stroke, CVD, and HF plus 4 mm Hg higher SBP compared with those treated with chlorthalidone 49…”
Section: Jnc 8 Recommendations 6 Tomentioning
confidence: 99%
“…On clinical grounds, as doxazosin is an ␣-blocker, dropping the CTDN-doxazosin trial is justified by the little or no support for ␣-blockers in recent hypertension guidelines. 11,36 For consistency, we choose to report results from the z statistic, which has the advantage of a more conservative P value.…”
Section: Osbp-adjusted Network Meta-analysismentioning
confidence: 99%
“…5,6 In the last several years, some have compared the drugs pharmacologically and have recommended CTDN rather than HCTZ. 3,[7][8][9][10][11][12] Two recent reanalyses of Multiple Risk Factor Intervention Trial (MRFIT) data have found CTDN to be superior to HCTZ in reducing cardiovascular events (CVEs) 13 and left ventricular hypertrophy. 14 However, no randomized, controlled trials have compared the 2 medications head to head with respect to CVEs.…”
mentioning
confidence: 99%
“…Although there are indications for specific classes of antihypertensive drugs for particular patients, such as diuretics for hypertensive African Americans, 1 there is no uniform agreement on the type of drug(s) that should be used when physicians choose an antihypertensive drug for newly diagnosed patients without specific indications for those drugs.…”
Section: Introductionmentioning
confidence: 99%